Model for multi-filamentary conduction in graphene/hexagonal-boron-nitride/graphene based resistive switching devices. (22nd May 2017) - Pan, Chengbin; Miranda, Enrique; Villena, Marco A; Xiao, Na; Jing, Xu; Xie, Xiaoming; Wu, Tianru; Hui, Fei; Shi, Yuanyuan; Lanza, Mario
Abstract: Despite the enormous interest raised by graphene and related materials, recent global concern about their real usefulness in industry has raised, as there is a preoccupying lack of 2D materials based electronic devices in the market. Moreover, analytical tools capable of describing and predicting the behavior of the devices (which are necessary before facing mass production) are very scarce. In this work we synthesize a resistive random access memory (RRAM) using graphene/hexagonal-boron-nitride/graphene (G/ h -BN/G) van der Waals structures, and we develop a compact model that accurately describes its functioning. The devices were fabricated using scalable methods (i.e. CVD for material growth and shadow mask for electrode patterning), and they show reproducible resistive switching (RS). The measured characteristics during the forming, set and reset processes were fitted using the model developed. The model is based on the nonlinear Landauer approach for mesoscopic conductors, in this case atomic-sized filaments formed within the 2D materials system. Besides providing excellent overall fitting results (which have been corroborated in log–log, log–linear and linear–linear plots), the model is able to explain the dispersion of the data obtained from cycle-to-cycle in terms of the particular features of the filamentary paths, mainly their confinement potential barrier height.